POSISI TIDUR MIRING EFEKTIF MENURUNKAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI POLI KIA RS RAHMAN RAHIM DESA SAIMBANG SUKODONO SIDOARJO - Santi Umi Rosdiani; Faridah Umamah (Jurnal Ilmiah Kesehatan, 2014)
The relationship sleeping sim position with back pain in pregnant women at third trimester in Rahman Rahim Hospital Sukodono Sidoarjo. The purpose of this study was to find out the relationship sleeping sim position with back pain in pregnant women at third trimester in Rahman Rahim Hospital Sukodono Sidoarjo.Study design use analytic with cross sectional approach, the population were pregnant women at third trimester by 25 respondents, number of sample were of 24 respondents taken by simple random sampling technique. The independent variable is the sleeping sim position and the dependent variable was back pain. Instrument use questionnaire. Data were analyzed using the Mann Whitney with a level of significance (α = 0.05).Study results the majority (66.7%) of pregnant women do not perform sleeping sim position regularly and half of them (50%) had moderate pain level. Mann Whitney test obtained P = 0.000 means there is a relationship between the sleeping sim position with back pain in pregnant women at third trimester. Irregularities of sleeping sim position will cause back pain, so suggested to pregnant women to perform side sleeping position regularly to prevent and manage back pain.